Boosting Online Visibility and Brand Awareness for Tarahan Village MSMEs via Google Business Profile and Hands-On Digital Literacy Support - Yuningsih, Yuningsih; Firdaus, Luthfi; Febrian, Angga; Julianti, Devi (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2025)
This program set out to help micro and small enterprises in Tarahan Village, South Lampung become easier to find, understand, and contact online by strengthening their Google Business Profile (GBP) presence and everyday branding habits. The core challenge was low discoverability on search/maps, inconsistent brand identity, and limited practical digital skills that kept market reach narrow despite growing internet use. Guided by brand salience and digital discoverability concepts (i.e., making the brand easier to notice, recognize, and retrieve in local search moments), we used a participatory, hands-on design: a rapid needs scan, co-designed training modules, live GBP demonstrations, guided implementation on each participant’s profile, and short-cycle follow-ups. This intervention combines GBP optimization with live mentoring and cultural storytelling, a rarely combined method in rural MSME digital capacity building, constituting the study’s novelty. Capacity gains were measured with pre/post tests, while profile progress and customer intent were tracked using GBP Insights (views, direction clicks, calls). After the training, participants claimed and completed their listings (core fields, photos, first posts) and activated reviews/messaging. Over May–October 2025, Insights recorded 88 views and 64 interaction events, mostly direction requests (61), with a September peak. Knowledge and confidence rose by ~17–22 points for every participant, indicating effective transfer of skills such as posting, photo curation, review replies, and reading Insights. We conclude that a lightweight, GBP-centered intervention—explicitly designed to heighten brand salience and reduce search friction—can deliver early, measurable gains in local discovery and establish routines to sustain them, with constraints (device/network variability and verification delays) manageable through periodic troubleshooting and shared visual assets.